Activation of (pro)renin by (pro)renin receptor in extracellular vesicles from osteoclasts - Jonathan B. Murray (Nature Portfolio, 2021)
Abstract The (pro)renin receptor (PRR) is a multifunctional integral membrane protein that serves as a component of the vacuolar H+-ATPase (V-ATPase) and also activates (pro)renin. We recently showed that full-length PRR, found as part of a V-ATPase sub-complex, is abundant in extracellular vesicles shed by osteoclasts. Here, we tested whether these extracellular vesicles stimulate (pro)renin. Extracellular vesicles isolated from the conditioned media of RAW 264.7 osteoclast-like cells or primary osteoclasts were characterized and counted by nanoparticle tracking. Immunoblotting confirmed that full-length PRR was present. Extracellular vesicles from osteoclasts dose-dependently stimulated (pro)renin activity, while extracellular vesicles from 4T1 cancer cells, in which we did not detect PRR, did not activate (pro)renin. To confirm that the ability of extracellular vesicles from osteoclasts to stimulate (pro)renin activity was due to the PRR, the “handle region peptide” from the PRR, a competitive inhibitor of PRR activity, was tested. It dose-dependently blocked the ability of extracellular vesicles to stimulate the enzymatic activity of (pro)renin. In summary, the PRR, an abundant component of extracellular vesicles shed by osteoclasts, stimulates (pro)renin activity. This represents a novel mechanism by which extracellular vesicles can function in intercellular regulation, with direct implications for bone biology.